Eksperimen Strategi Pembelajaran Snowball ThrowingDan Think Pair Check Terhadap Prestasi Belajar SiswaDitinjau Dari Minat Siswa Pada Siswa Kelas VII SemesterGenap SMPN 1 Selogiri Tahun 2014 - Kinanthi, Dyah Ayu; , Drs. Slamet HW, M.Pd (2015)
This research aims to examine the influence of learning strategies Snowball Throwing and Think Pair Check of student learning achievement, examine the students interest in influence to the achievement of learning, examine the interaction of learning strategies Snowball Throwing and Think the Pair Check and interest of students towards the learning achievements of students. This research population Class VII 1 Selogiri SMP. Sample research 30 grade VII F as a class experiment and 30 students a Class VII G class controls with random sampling techniques. Data collection method using quesioner, tests and documentation. Trial results of tests meet the test validity and reliability. The balance test using a t-test shows the both of class in a State of balance. The average grade obtained experimental 67,4 and control class 60,30. Test precondition is met, the test of normality by the method of Lilliafors and its homogeneity test with significance level of Bartlett method with 5%. Results of the analysis using the variance hypothesis two way cells do not match obtained Fa = 0,124, Fb = 0,155, and Fab = 0,018 shows all of < Fα then all H0 are received. It was concluded there was no influence of learning strategies Snowball Throwing and Think the Pair of student learning achievement check. There is no influence of the interest of students towards the learning achievements of students. There is no interaction between the learning strategy Snowball Throwing and Think the Pair check and interest of students towards the learning achievements of students.